Failure to tolerate continuous subcutaneous treprostinil in pediatric pulmonary hypertension patients - Julia McSweeney; Elizabeth Colglazier; Jasmine Becerra; Brienne Leary; Kathleen Miller‐Reed; Stephen Walker; Katy Tillman; Melissa Magness; Michelle Ogawa; Whitney Bannon; Tisha Kivett; Emma O. Jackson; et al. (Pulmonary Circulation, 2023)
Abstract Continuous subcutaneous (SubQ) treprostinil is an effective therapy for pediatric patients diagnosed with pulmonary hypertension (PH). To date, the clinical characteristics and factors associated with failure to tolerate this therapy have not been described. The purpose was to describe patient‐reported factors contributing to SubQ treprostinil intolerance in pediatric patients with PH. A retrospective descriptive study was performed at 11 participating sites in the United States and Canada for patients younger than 21 years of age diagnosed with PH who failed treatment to tolerate SubQ treprostinil between January 1, 2009, and December 31, 2019. All data were summarized using descriptive statistics. Forty‐one patients met the inclusion criteria. The average age at SQ treprostinil initiation, and length of treatment, was 8.6 years and 22.6 months, respectively. The average maximum dose, concentration, and rate were 95.8 ng/kg/min, 6.06 mg/mL, and 0.040 mL/h, respectively. The reasons for failure to tolerate SubQ treprostinil included intractable site pain (73.2%), frequent site changes (56.1%), severe site reactions (53.7%), infections (26.8%), and noncompliance/depression/anxiety (17.1%). Thirty‐nine (95.1%) patients transitioned to a prostacyclin therapy with 23 patients transitioning to intravenous prostacyclin, 5 to inhaled prostacyclin, 5 to oral prostacyclin, and 7 to a prostacyclin receptor agonist. A subset of pediatric PH patients failed to tolerate SubQ treprostinil infusions despite advances in SubQ site maintenance and pain management strategies. Intractable site pain, frequent SubQ site changes, and severe localized skin reactions were the most common reasons for failure.